A qualitative model for the biological community of the Northern Gulf of California, Mexico: potential fisheries effects on the ecosystem - Espinoza-Tenorio, Alejandro (2015)
Ecosystem-based management (EBM) is one of the main paradigms under which the world’s fisheries have been redesigned. However, successful implementation of EBM has been limited due to the inherent complexity of ecological systems as well as the need to have enough information to build and analyze complex models. To successfully implement EBM in fisheries, countries such as Mexico need to design and promote management tools consistent with their social and natural context in a way that they can take advantage of the capabilities of their fishery systems. In this paper we used a qualitative model (Loop Analysis) to examine the ecosystem implications of fishery on some members of a marine community.  A model for the biological community of the Northern Gulf of California (NGC) was constructed, based on six fishery groups and a conservation group. Model predictions allowed assessing both direct and indirect effects from harvesting different fishery groups, as well as identifying those fisheries that might present a conflict when operating simultaneously. The qualitative nature of the model allowed incorporating local ecological knowledge (LEK) as a source of information, fostering the future involvement of stakeholders in the design of management strategies. The proposed ideas may be useful to generate goals regarding resource exploitation and conservation and also provide a guide to generate management strategies based on the knowledge of the ecosystem.